The Law of Instant Equality of the Purchasing Power of Money - V. N. Yusim (Вестник Российского экономического университета имени Г. В. Плеханова)
The article proves effectiveness of the law of instant equality of money unit buying capacity. It is shown that the law explains the phenomenon of money unit arising as a value measure and, consequently, grounds the unity of money arising principles as virtual value measure and real measures, i.e. physical quantities. The author analyzes historical evolution of money types and provides arguments that it is underlain by changing methods of fixing the money unit buying capacity. It is demonstrated that the quality of money units and, thus money systems, changes, when the method is altered. It is stated that the phenomenon of arising a unique buying capacity of all money units of the national currency at any moment of time possesses the same character as the method of providing the unity of measuring physical quantities. Consequently, the author comes to the conclusion that money units acting as a cost value should obey the basic principles of science dealing with measurements, i.e. ‘metrology’. The article grounds that methods providing the unity of value measuring through money, as well as methods providing the unity of measuring physical quantities correlate with the level of available technological possibilities. It could be concluded that due to the correlation requirement a new type of virtual money with constant buying capacity or ‘virtual gold’ will come into being. It is underlined that virtual gold can be used only within the frames of a brand new, i.e. bi-currency money system. It is characterized by simultaneous functioning of traditional paper money and previously unknown money with constant buying capacity.